Unveiling the Effects of Natural Disasters and Nuclear Energy on the Secondary Sex Ratio: A Comprehensive Review - Iasonas Dermitzakis; Paschalis Theotokis; Efthymia Delilampou; Evangelos Axarloglou; Sofia Gargani; Dimosthenis Miliaras; Maria Eleni Manthou; Soultana Meditskou (Life)
The secondary sex ratio (SSR), defined as the ratio of male to female births in a population, has long been a subject of scientific inquiry due to its potential as a health indicator. The interplay between catastrophic events and the delicate balance of male and female births presents a nuanced and compelling study area. Natural disasters, such as earthquakes, hurricanes, floods, and volcanic eruptions, have been known to disrupt ecosystems and human populations, leading to both short-term and long-term consequences. Studies have suggested a potential influence of these disasters on the SSR, with varying degrees of impact observed across different regions and disaster types. Similarly, nuclear accidents, such as the infamous Chernobyl disaster, have sparked interest in their potential effects on human health and development. The release of radioactive materials into the environment can have far-reaching consequences, including impacts on reproductive outcomes. Through a rigorous examination of the existing literature, the present review aims to synthesize current knowledge on the impacts of natural disasters and nuclear accidents on the SSR and unravel the mechanisms that explain SSR fluctuations. By shedding light on the diverse influences shaping the SSR, this narrative review contributes to a deeper appreciation of the intricate interplay between environmental, biological, and societal factors that determines the SSR, calling for targeted strategies to mitigate potential adverse effects on sex ratios in the aftermath of such events.